Dry season circulation-type classification applied to precipitation and temperature in the Peruvian Andes - Bonshoms M. (2020)
We present the first systematic classification of circulation regimes that characterize the Tropical Andes during the dry season (May–August). We apply the hierarchical k-means clustering method to ERA-Interim reanalysis data of daily mean geopotential height at 500- and 200-hPa levels for the period 1981–2015. Specifically, by combining the variability in intensity and location of geopotential anomalies we identify 12 circulation types (CTs). We then establish the relationship between the CTs and surface conditions in the Peruvian Andes (PA) analysing high-resolution gridded datasets of daily mean temperature and rainfall. Our results indicate that intense precipitations and low minimum temperatures are often associated with an Upper Tropospheric Trough (UTT) centred at subtropical latitudes (~30°S) and between 80° and 70°W of longitude. Moreover, drier and warmer conditions across the entire PA region are largely associated with three anticyclonic CTs. Strong negative anomalies in daily maximum (minimum) temperatures can be related to the effect of day (night) cloudiness in the radiative balance, but also to subtropical cold air advections favoured by the UTT. While CTs featuring warmer (colder) conditions have become more (less) frequent in the last decades of the record, there is no systematic link between positive or negative trends in occurrence and the wetter and drier character of the CTs. The annual frequencies of 10 CTs are significantly correlated with El Niño-Southern Oscillation, with warmer and drier (cooler and wetter) CTs generally preceded by an El Niño (La Niña) in the previous wet season. © 2020 Royal Meteorological Society